Outcome of Early vs. Delayed Invasive Intervention in Acute Coronary Syndrome Patients Attending a Selected Specialized Hospital: A Comparative Study (Cardiovascular Journal, 2019)
Background: This study was to compare the outcome of early versus delayed invasive intervention in acute coronary syndrome (ACS) patients.Methods: A total of 200 patients with ACS underwent early intervention group (d”24 h, n=100) and delayed intervention group (>24 to 72 h, n=100) after percutaneous coronary intervention (PCI) were enrolled. The probable outcomes were a composite of re-infarction, acute LVF, recurrent ischemia, repeat revascularization, bleeding, stroke or death at 30 days.Results: Male were predominating (74%vs26%). Left anterior descending artery was the commonest infarct related artery in both groups (p=0.114). Cardiac markers, Cardiogenic shock, Acute left ventricular failure (LVF) and ventilator requirement were significantly higher (p=0.007, p=0.060, p=0.009, p=0.002) and mean duration of hospital stay was longer (p